The Labor Market Integration of Migrants in Europe : New Evidence from Micro Data - Ho, Giang; Turk-Ariss, Rima. (Washington, D.C. : International Monetary Fund, 2018)
This paper presents novel empirical evidence on the labor market integration of migrants across Europe. It investigates how successfully migrants integrate in 13 European countries by applying a unified framework to analyze a rich micro dataset with over ten million individuals surveyed between 1998 and 2016. Focusing on employment outcomes, we document substantial heterogeneity in the patterns of labor market integration across host countries and by migrant gender and origin. Our results also point to the importance of cohorts and network effects, initial labor market conditions, and the differential impact of education acquired domestically and abroad in determining migrants' subsequent employment prospects. The analysis has implications for the design of effective integration policies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet